Theoretical and methodological foundations for the research of office documentation on problems of Caucasian studies - Anzhela Arikovna Zhurtova (Кавказология, 2023)
The article examines the theoretical and methodological foundations of the study of office evidence through the analysis of sources on the history of the North Caucasus. The author defined the concept, types and methods of studying office documentation, carried out a historiographical review of the main studies devoted to the development of a theoretical basis for the study of this type of sources. She paid special attention to the study of the experience accumulated in Caucasian studies in the study of office materials of Russian administration in the North Caucasus at the end of the 18th – 19th centuries. In particular, the author analyzed the works of A.Kh. Abazov, E.G. Muratova, T.A. Kolosovskaya, Z.Zh. Glasheva, D.M. Alkhasova and others, in which they, thanks to the use of methods of classification, generalization, functional and interdisciplinary analysis, etc. carried out external and internal criticism of office documentation. The author concluded that a comprehensive source analysis of office materials using special historical and interdisciplinary methods and approaches is required.